Analisis Dampak Rasio Keuangan Terhadap Total Return Saham Pada Perusahaan Industri Manufaktur Yang Membagikan Dividen (GEMA EKONOMI, 2023)
Every business owner tries to make his business successful, one of which is by opening stock opportunities. The availability of investors as company shareholders, whose financial contributions can help manufacturing companies' ability to operate, so that they can influence the company's success. Everyone who puts money into a company with the hope of getting a stock return. Therefore, researchers are interested in testing the impact analysis of financial ratios on total stock returns in manufacturing industry companies that pay dividends. The purpose of this study is to gain knowledge about the impact of financial ratios on total stock returns, in manufacturing companies that issue dividends. Descriptive quantitative methods were used in this research, and data were collected by analyzing the financial statements of fifty manufacturing companies selected using a probability-based random selection procedure. Then SPSS is used to analyze the collected data, and the results show that the CR, DER, ROA, and ROE metrics all have a positive and significant influence (with a value of 89.3%) on the total return on shares of manufacturing companies that pay dividends.